Gambaran Self -Esteem Remaja Kasus Pembunuhan di Lembaga Pembinaan Khusus Anak Kelas 1 Blitar - Putri, Aurellya Yuliana; Helmalia, Nabila; Cempaka, Lutfia; Dzakiya, Ainin Hana; Rahayu, Putri; Rahma, Rezka Arina (Universitas Negeri Malang, 2026)
Adolescents who are searching for their identity will experience a situation of identity versus identity confusion, which in some adolescents creates a self-image through bad behavior that leads to criminal acts. The number of murder cases committed by adolescents in murder East Java province throughout the year continues to increase. This study aims to determine the psychological condition of self-esteem among juvenile offenders before and after committing murder. This study uses a qualitative approach with a phenomenological study method at the LPKA Kelas 1 Blitar. Data were collected through in-depth interviews with three informants (E, K, W). Data analysis was performed using thematic analysis, and data validation was performed using time triangulation. The findings indicate that there are variations in the dynamics of self-esteem among the three informants. These variations are reflected in the different behavioral patterns displayed by each informant. In addition, external factors, such as parenting styles and unhealthy peer environments, were identified as contributing backgrounds to the homicide committed by the three informants. The meanings attributed by the three informants after committing murder were that E and W admitted to regretting their actions, while K admitted to feeling relieved after committing the act. Abstrak Remaja dalam kondisi mencari jati diri akan mengalami situasi identitas vs kebingungan identitas yang pada beberapa remaja menciptakan citra diri melalui tindakan buruk yang mengarah pada perbuatan kriminal. Angka kasus pembunuhan yang dilakukan oleh remaja di Provinsi Jawa Timur sepanjang tahunnya terus meningkat. Penelitian ini ditujukan untuk mencari tahu kondisi self-esteem yang dimiliki Anak Didik Pemasyarakatan (Andikpas) sebelum dan setelah melakukan pembunuhan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi fenomenologi di LPKA Kelas 1 Blitar. Data dikumpulkan melalui wawancara mendalam dengan tiga orang partisipan (E, K, W). Analisis data dilakukan menggunakan analisis tematik, validasi data menggunakan triangulasi waktu. Hasil penelitian menemukan bahwa terdapat variasi dinamika self-esteem pada ketiga informan. Variasi tersebut tercermin dalam pola perilaku yang berbeda pada masing-masing informan. Selain itu, terdapat faktor eksternal berupa pola asuh serta lingkungan pertemanan yang kurang sehat yang menjadi latar belakang ketiga informan melakukan pembunuhan. Adapun pemaknaan yang ditujukan kepada ketiga informan setelah melakukan pembunuhan, yakni E dan W mengaku menyesal atas tindakannya, dan K mengaku lega setelah melakukan perbuatannya.